NILAI-NILAI BIMBINGAN DALAM HADIH MADJA - Adnan, Adnan (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2019)
This study aims to reveal, study, and analyze holistically the values of guidance in Hadih Madja. This research method is qualitative with content analysis techniques. The data of this study were collected through primary sources (a collection of hadih madja) and secondary, namely the literature related to the discussion of this study. The results showed: First, Hadih Madja is an oral literature that contains advice, lessons, wisdom, and moral values in the life of the people of Aceh, including law, religion, social, customs, education, counseling, political guidance, and heroism. Secondly, the values of guidance in Hadih Madja are values that can be a reference, reference, and moral source for modern Acehnese society. Third, there are some guidance values in Hadih Madja, namely, the value of religiosity, never giving up, courage, trust, altruism, patience, and love for the motherland.